Pain Management in Older Adults A Nursing Perspective (Perspectives in Nursing Management and Care for Older Adults,, 2018)
This book addresses relevant issues to enhance pain management nurses need to advocate for effective pain treatment in the elderly. Significant changes in the evolving nursing and healthcare environment require adequate information on this topic, as pain is a very challenging area. As other care professionals, nurses are daily confronted with issues on pain assessment and management. This volume offers an overview within an evolving health environment, in which nurses dealing with pain play a growing role. It showcases best practices in pain assessment and management, details non pharmacological and pharmacological treatments. It also addresses core issues defined by the International Association for the Study of Pain (IASP), such as knowledge translation, that are most relevant for clinical nurses, student nurses, nurse researchers as well as other care professionals.